INVESTIGATION OF PALM KERNEL SHELL AS PARTIAL REPLACEMENT FOR AGGREGATE IN ASPHALTIC CONCRETE (Malaysian Journal of Civil Engineering, 2018)
Palm kernel shell (PKS) is used as a partial replacement for fine and coarse aggregates in asphalt. Crushed palm kernel shell (CPKS) and PKS were added at 20, 40, 50, 60 and 80% by weight of total aggregates to partially replace the fine and coarse aggregates in asphaltic concrete. Properties such as aggregate impact value, aggregate crushing value, bitumen penetration test and Marshall Stability test were performed in accordance with ASTM D 6927 – 06. From the analysis, CPKS has a stability value of 1,033kg at 20% replacement, 660kg, 646kg, 566kg and 528kg at 40%, 50%, 60% and 80% replacements respectively; while, PKS has a stability value of 2,860kg at 20% replacement, 2,398kg, 2,343kg, 2,156kg and 2,123kg at 40%, 50%, 60% and 80% replacements respectively. Comparing with ASTM D448-12, PKS can be used as alternative material for coarse aggregate for light, medium and heavy traffic roads while, 20% of CPKS can be used as fine aggregates in heavy traffic road and 60% in medium traffic roads. It is therefore recommended that this agro-based product can be used as partial alternate material in asphaltic concrete to reduce the cost of construction.